Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2196/28116
|View full text |Cite
|
Sign up to set email alerts
|

Using an Individual-Centered Approach to Gain Insights From Wearable Data in the Quantified Flu Platform: Netnography Study

Abstract: Background Wearables have been used widely for monitoring health in general, and recent research results show that they can be used to predict infections based on physiological symptoms. To date, evidence has been generated in large, population-based settings. In contrast, the Quantified Self and Personal Science communities are composed of people who are interested in learning about themselves individually by using their own data, which are often gathered via wearable devices. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Wearable devices have become increasingly popular for the monitoring of all sorts of activities such as fitness, sleep and feeding habits (Asimakopoulos et al 2017, Dias et al 2018, Peake et al 2018. More recently these devices have shown some promising results in term of health monitoring including neurological disorders, infection, heart and respiratory condition detection (Behar et al 2019, Mishra et al 2020, Tzovaras et al 2021. A Recent large scale study from Apple (Perez et al 2019) showed that tachiograms (equivalent to our RR Baseline ) depicted a positive predictive value for AF of 0.84.…”
Section: Discussionmentioning
confidence: 99%
“…Wearable devices have become increasingly popular for the monitoring of all sorts of activities such as fitness, sleep and feeding habits (Asimakopoulos et al 2017, Dias et al 2018, Peake et al 2018. More recently these devices have shown some promising results in term of health monitoring including neurological disorders, infection, heart and respiratory condition detection (Behar et al 2019, Mishra et al 2020, Tzovaras et al 2021. A Recent large scale study from Apple (Perez et al 2019) showed that tachiograms (equivalent to our RR Baseline ) depicted a positive predictive value for AF of 0.84.…”
Section: Discussionmentioning
confidence: 99%
“…This project was begun by members of the Quantified Self and Open Humans communities from outside of academia. It developed into a larger co-creation process that involved a heterogeneous community developing a collective self-tracking system to monitor symptoms of infection alongside wearable sensor data (Greshake et al, 2021). In this example, the team of volunteer contributors was highly diverse in terms of professions, competences and skills, and career stage.…”
Section: Map Of Shared Skills Across Covid-19 Projects On the Just On...mentioning
confidence: 99%
“…At the same time, a software developer volunteered his expertise to implement numerous data import options for different wearable devices; a mobile app developer contributed by creating a dedicated app for smartphones; and a trained journalist dedicated time to do outreach and recruitment. A sociologist investigated the co-creation process, and the project recently culminated in an academic publication that he transdisciplinary collaboration that was based on volunteer contributions from a variety of disciplines and included contributors from across the globe (Greshake et al, 2021). In addition, the project outcome was the prototype implementation.…”
Section: Map Of Shared Skills Across Covid-19 Projects On the Just On...mentioning
confidence: 99%
“…Personal science can yield unique insights for individuals [ 11 , 12 ] and enhance their sense of agency and quality of life [ 13 ]. Moreover, self-research can drive the development of new approaches or tools [ 14 , 15 ], inspiring clinical research with these tools and ideas [ 16 ].…”
Section: Introductionmentioning
confidence: 99%